1976
DOI: 10.1111/j.1365-2842.1976.tb00943.x
|View full text |Cite
|
Sign up to set email alerts
|

Etching of enamel prior to application of fissure sealants

Abstract: Acid etching has been shown to be necessary to increase the bond strength of the polymeric fissure sealants Epoxylite 9075 and Nuva Seal to enamel. For Nuva Seal or Epoxylite 9075 it would appear that it does not matter which concentration between the concentration levels of 30 and 70% is used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1977
1977
1982
1982

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Adipramoto, Beech & Hardwick (1975) obtained similar bond strengths when 2, 30 and 50% solutions of phosphoric acid were used as the etchant but 16% concentration gave the highest bond strengths. Williams, von Fraunhofer & Winter (1976), however, found that for fissure sealants, there was no difference in bond strength for concentrations between 30 and 70 % of phosphoric acid solution.…”
Section: Introductionmentioning
confidence: 94%
“…Adipramoto, Beech & Hardwick (1975) obtained similar bond strengths when 2, 30 and 50% solutions of phosphoric acid were used as the etchant but 16% concentration gave the highest bond strengths. Williams, von Fraunhofer & Winter (1976), however, found that for fissure sealants, there was no difference in bond strength for concentrations between 30 and 70 % of phosphoric acid solution.…”
Section: Introductionmentioning
confidence: 94%
“…Adipranoto, Beech & Hardwick (1975) showed that a 2 % phosphoric acid solution gave similar bond strengths to 30% and 50% solutions and reported that a 16% concentration was the most effective pretreatment concentration. Williams, von Fraunhofer & Winter (1976), however, found that for two proprietary fissure sealants no difference in bond strength was found for phosphoric acid concentration levels in the range of 30 and 70% acid solutions.…”
Section: Introductionmentioning
confidence: 99%